"Living Theology" – Everyday Life, Challenges and Resources among International Pentecostals in Stockholm - Westerlund, Katarina (PentecoStudies, 2023)
This article explores challenges and resources among international Pentecostals living in the capital of Sweden. The analysis builds on fieldwork carried out in 2019 in an Arabic and an African Pentecostal church the Stockholm. Using lived religion as a theoretical tool, challenges related to the Swedish culture are explored, revealing experiences of discrimination and intolerance of both the informants’ origin and Pentecostal faith, and thereby questioning personal and religious identity. Resources among the international Pentecostals are found in the church community forming an extended family with both practical, emotional, and spiritual support, that provides meaning and purpose. Furthermore, the spiritual dimension of lived religion is highlighted as foundational for the international Pentecostals as Living theology expressed in their lives. The article contributes by a strong practice approach and by highlighting the meaning of social and cultural context for Pentecostal Christianity.